GENERAL FIXED POINT THEOREMS FOR PAIRS OF EXPANSIVE MAPPINGS WITH COMMON LIMIT RANGE PROPERTY IN G - METRIC SPACES - Popa, V.; Patriciu, A.-M. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2018)
In this paper two general fixed point theorems for pairs of extensive mappings with common limit range property in G - metric spaces are proved. In the last part of this paper, as applications, two general fixed point results for mappings satisfying extensive conditions of integral type are obtained.